Construction of polyallophanate vitrimers from poly(urea carbonate) via group revival induced crosslinking. (5th December 2021) - Zhang, Zhihuang; Lin, Chenxi; Hou, Rui; Tang, Donglin
Graphical abstract: Group revival induced crosslinking (GRIC) is a novel strategy in the construction of vitrimers, directly from linear polymers, e.g., from poly(urea carbonate)s, without adding any crosslinker. The poly(urea carbonate) vitrimers are found to be tough and reprocessible. Highlights: Group revival induced crosslinking (GRIC) is a novel strategy for construction of vitrimers, directly from linear polymers without any additional crosslinker. Poly(urea carbonate)s are of special structure in which urea and carbonate align alternatively in the backbone, which is different from other conventional polycarbonate polyurea. The networks with allophanate crosslinkers and constructed via GRIC from poly(urea carbonate)s are confirmed to be vitrimers. GRIC strategy can be extended to broader applications, such as in the modification of linear polyurethanes or polyureas, in the high value added modification of recycled polyurethanes, etc. Abstract: Vitrimers are now believed to be the third class of polymers, besides thermosets and thermoplastics, owing to their crosslinking structure but processible property. A new strategy, namely group revival induced crosslinking (GRIC), was introduced in this work for the construction of polyallophanate vitrimers from two poly(urea carbonate)s (PUC-5 and PUC-6). Different from conventional polycarbonate polyurea, PUCs are structured by urea and carbonate groups alternatively and repeatedly. Under the catalysis of 1, 5, 7- triazabicyclo[4.4.0]dec-5-ene (TBD), the NH groups in the PUC backbones is activated and therefore become revival to attack the carbonate groups to form allophanate crosslinkers and free OH groups as well. The reversible transallophanation between the allophanate and OH groups allows the obtained networks to be reprocessible. The moduli of both networks grows linearly with 1/T, which fits with the unique characters of vitreous materials. PUC-6 keeps similar appearance and similar mechanical properties (E: ∼60 MPa; σb : 20 MPa; εb : ∼350%) after 1st, 2nd and 3rd compression molding. It reveals from this work that vitrimers can be easily constructed via GRIC followed with dynamic transallophanation in polymers bearing both urea and carbonate groups, or even in linear polyurethanes.